2018
DOI: 10.1152/ajprenal.00149.2018
|View full text |Cite
|
Sign up to set email alerts
|

The chemokine receptor CX3CR1 reduces renal injury in mice with angiotensin II-induced hypertension

Abstract: The role of CXCR1, also known as fractalkine receptor, in hypertension is unknown. The present study determined the role of the fractalkine receptor CXCR1 in hypertensive renal and cardiac injury. Expression of CXCR1 was determined using CXCR1 mice that express a GFP reporter in CXCR1 cells. FACS analysis of leukocytes isolated from the kidney showed that 34% of CD45 cells expressed CXCR1. Dendritic cells were the majority of positive cells (67%) followed by macrophages (10%), NK cells (6%) and T cells (10%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…For example, fractalkine (CX3CL-1) has been implicated in the pathogenesis of hypertension 40 and hypertension-related renal injury. 41 Our finding that this chemokine was associated with nocturnal systolic BP, diastolic BP, and percent nocturnal dip suggests that CX3CL-1 is not only a therapeutic target for multiple inflammatory conditions, 42 but also a potential therapeutic target for hypertension.…”
Section: Discussionmentioning
confidence: 86%
“…For example, fractalkine (CX3CL-1) has been implicated in the pathogenesis of hypertension 40 and hypertension-related renal injury. 41 Our finding that this chemokine was associated with nocturnal systolic BP, diastolic BP, and percent nocturnal dip suggests that CX3CL-1 is not only a therapeutic target for multiple inflammatory conditions, 42 but also a potential therapeutic target for hypertension.…”
Section: Discussionmentioning
confidence: 86%
“…While some studies suggest profibrotic action after ischemia reperfusion injury (Furuichi et al 2006 ) and more recently, after oral fructose treatment (Yu et al 2018 ), both pro- and antifibrotic effects of genetic CX3CR1 deletion were reported in unilateral ureteral obstruction in mice (Engel et al 2015 ; Peng et al 2015 ). Also in kidney fibrosis induced by hypertension, while an earlier report describes aggravation by CX3CR1 in DOCA salt–treated mice (Shimizu et al 2011 ), a more recent study found less renal hypertensive damage in unilaterally nephrectomized angiotensin II-infused mice on a high salt diet in the presence of CX3CR1 than in its absence (Ahadzadeh et al 2018 ). There was no difference in cardiac fibrosis.…”
Section: Pathophysiologic Role In Kidney Diseasementioning
confidence: 98%
“…The authors of the study speculated that CX3CR1 has a protective role against liver fibrosis via infiltrating monocytes in the injured liver. Although CX3CL1/CX3CR1 axis has been linked to pathogenesis of chronic inflammatory diseases, there are some studies also that showed the anti‐inflammatory features of CX3CR1 29,30 . Considering this information, we may suggest that elevated levels of CX3CR1 in serum may reflect homeostasis without binding its ligand, CX3CL1.…”
Section: Discussionmentioning
confidence: 97%